Adjuvant 5FU plus levamisole in colonic or rectal cancer: improved survival in stage II and III - Taal, B G (Nature Publishing Group, 2001)
Based on the first favourable results of adjuvant therapy of 5FU plus levamisole in Dukes C colonic cancer in 1990, we conducted a prospective trial. 1029 patients were randomised to receive one year 5FU plus levamisole or no further treatment following curative surgery for stage II or III colon (n = 730) or rectal cancer (n = 299). 45% were in stage II and 55% in stage III. With a median follow-up of 4 years and 9 months a significant reduction in odds of death (25%, SD 9%, P = 0.007) was observed for those with adjuvant treatment (65% at 5 year) compared to the observation group (55%). Improved relative survival was present in stage III (56% vs 44%), and in stage II patients (78% vs 70%). In rectal cancer a non-significant difference in disease-free or overall survival was observed. Distant metastases developed in 76%, while local recurrence alone occurred in 14%. An early start of adjuvant treatment (< 4 weeks) did not affect results. Compliance to 5FU plus levamisole was 69%. Severe toxicity did not occur. In conclusion, one year 5FU plus levamisole was of benefit in stage II and III colonic cancer; in rectal cancer a significant positive effect could not be demonstrated. © 2001 Cancer Research Campaign  http://www.bjcancer.com